Design of Critical Thinking Ability Questions with Colorful Ribbon Context for Hearing Impaired Students - Hedia Rizki; Meirisa Sahanata; Fitri Kumala Dewi; Elis Muslimah Nuraida (JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study aimed to develop a mathematics test instrument that assesses the critical thinking skills of hard-impaired students using a Realistic Mathematics Education (RME) approach in a colored ribbon context. The research employed a design research method with a development type, consisting of the preliminary and prototyping stages, including self-evaluation, expert review, and one-to-one. The instrument was developed based on Ennis’s (1985) critical thinking indicators, comprising five items adapted to the visual characteristics of Grade XI deaf students at SMALB. Content and language validation by experts confirmed the qualitative validity of the items. A limited trial (one-to-one) involving three hearing-impaired students revealed that the items were understandable and suitable, particularly due to the use of simple language, visual aids, and concrete objects. In conclusion, the critical thinking questions based on the RME approach and visual context are effective for hearing-impaired students and offer an alternative assessment tool that accommodates their sensory limitations. Keywords: critical thinking; hearing-impaired students; realistic mathematics education.